Aneurysm sac enlargement 16 years after endovascular aortic aneurysm repair due to late type IIIb endoleak: A case report. (2018) - Murakami, Yuri; Toya, Naoki; Fukushima, Soichiro; Ito, Eisaku; Akiba, Tadashi; Ohki, Takao
Highlights: We diagnosed a type IIIb endoleak and performed a secondary relining procedure with an ePTFE device. Compared with the type IIIb endoleaks discussed in past reports, the present case occurred with a much longer delay. Relining using an ePTFE endograft may be considered an effective for type IIIb endoleaks. Abstract: Introduction: We report a case with delayed aneurysm sac enlargement 16 years after EVAR due to late type IIIb endoleak. Presentation of Case: An 84-year-old man was referred to our hospital with an aneurysm sac enlargement after endovascular aortic aneurysm repair (EVAR), which had been performed at another hospital 18 years earlier using the Zenith endograft. Computed tomography (CT), after EVAR had shown significant sac shrinkage. However, the patient presented with delayed aortic aneurysm enlargement due to an assumed endoleak. Duplex ultrasound showed a type IIIb and a type Ib endoleak. We performed a re-intervention with an AFX endograft, for relining due to persistent type IIIb endoleak. Discussion: Compared with the type IIIB endoleaks discussed in past reports, this case occurred with a much longer delay. Although CT could not identify the type of endoleak, duplex ultrasound led us to diagnose the type IIIb endoleak. Conclusion: Relining using an ePTFE endograft may be considered an effective procedure for type IIIb endoleaks. Duplex ultrasound is useful for determining endoleak types.